Orbital TFE3-Rearranged Perivascular Epithelioid Cell Tumor: A Case Report and Review of the Literature. (20th December 2021) - Feu-Basilio, Silvia; Matas, Jessica; Dotti-Boada, Marina; Toll, Agustin; Larque, Ana-Belen; Pigem, Ramon; Ortiz-Perez, Santiago
Abstract: Perivascular epithelioid cell tumors (PEComas) are infrequent mesenchymal neoplasms that have particular histological and immunohistochemical features. Only a few cases have been described in the eye and orbit. This report presents a 28-year-old man who consulted for a painless left orbital mass. With the presumptive diagnosis of cavernous hemangioma, a surgical excisional biopsy was performed. Histopathological examination showed a well-delimited tumor composed of epithelioid cells with an eosinophilic cytoplasm and oval nucleus. The tumor cells stained diffusely for HMB-45 and transcription factor E3 (TFE3) and were focally positive for actin. There was no reactivity to S100 or desmin. Genetic testing revealed a TFE3 rearrangement. Based on these results, an extremely rare orbital TFE3-rearranged PEComa was diagnosed. Although no recurrence was seen at last follow-up, a review of the literature shows experience is limited regarding orbital PEComas and their malignant potential. Further research is needed to establish management guidelines, their association with the tuberous sclerosis complex, and the role of genetic mutations such as TFE3 rearrangement.